Respiratory-Kinesiological Rehabilitation in the Early Periods after Cardiosurgical Interventions - G. P. Plotnikov; Ye. V. Malakhov; B. L. Hayes; Ye. V. Grigoryev; L. S. Barbarash (Общая реаниматология)
Objective: to substantiate an algorithm for early respiratory-kinesiological rehabilitation used in the multimodality treatment of cardiosurgical patients developing multiple organ dysfunction syndrome (MODS). Subjects and methods. A randomized study was performed in 90 cardiosurgical patients with postoperatively evolving MOD, who were mechanically ventilated. In addition to conventional intensive therapy, these patients received an original complex of early respiratory-kinesiological rehabilitation. Results and Conclusion. The study has demonstrated the impact of respiratory and kinesiological rehabilitation on the course of a postoperative period: normalization of autonomic status-evaluating tests (from Д13±1.7 to Д7.5±4.9), endurance coefficient (21.8±9.9 to 16.5±7.2) in the study group versus 20.5±10.2 to 18.3±6.5 in the control group), adaptation potential (from the poor values 3.3±2.7 to the tension ones 2.9±2.2 scores since day 2; this trend was observed in the control group since postoperative day 5); improvement of gas transport parameters during exercises and within at least 6 hours after this, without changing artificial ventilation (AV) modes (improvement of the values of DO2I (by 12.3±4.5% of the baseline value), VO2I (by 8.8±5.3% of the baseline value), O2ER (by 16.5±8.5% of the baseline value); accelerated switching to assisted ventilation modes (78.6±18.3 hours (the start of assisted AV modes) in the study group versus 92.1±22.7 hours in the control one); a shorter length of stay in an intensive care unit (9.55±4.3 versus 14.2±5.5 days). The positive result from a primary pharmacoeconomic analysis for surviving patients is shown. Key words: rehabilitation, multiple organ dysfunction, cardiac surgery.